Chemical composition of germinating Tunisian almond (Prunus Amygdalus Mill.) seedlings oil - Dhouibi, Refka; Oueslati, Hanen; Bahri, Senda; Jabou, Khaled; Bahri, Sellema (Kuwait Journal of Science, 2021)
Almond trees (Prunus Amygalus Mill) are a rich source of many essential nutrients. However, there is no much information on the biochemical composition of almond varieties, especially at the germination stage. Therefore, this study was conducted to determine the chemical components of Tunisian almond seedlings such as the content of oils, proteins, fatty acids and triglycerides during germination. Results indicated that the oleaginous seeds are rich in oil (55 to 65% of the dry mass) and crude protein (21.825 mg/mL). The dominant polyunsaturated fatty acids are oleic and linoleic acids which represent 64.53% and 24.38% respectively, while palmitic acid is the most dominant saturated fatty acid with 7.65% of the total fatty acids. In addition, the main molecular types of triglycerides detected by LC analysis are trioline (32.3%) and dioleolinolein (24.0%), followed by palmitodiolein (12.5%) and oleodilinolein (12.6%.) Some physico-chemical properties have been studied, consequently, we found that almond oil remains stable, thus preserving its quality and nutritional value even when the transition from dormancy to germination. On another hand, we also detected the presence of a low lipolytic activity which is maximum at the step 3 days of germination (4.66 mUI). All these results indicate that almond oil could play an important role in a human healthy nutrition due to the presence of unsaturated fatty acids.